2006
DOI: 10.1242/jcs.02901
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of paracellin-1 at Ser217 by protein kinase A is essential for localization in tight junctions

Abstract: Although paracellin-1 (PCLN-1) is known to have a crucial role in the control of Mg2+ reabsorption in the kidney, the molecular pathways involved in the regulation of PCLN-1 have not been clarified. We used FLAG-tagged PCLN-1 to investigate these pathways further, and found that PCLN-1 is phosphorylated at Ser217 by protein kinase A (PKA) under physiological conditions in Madin-Darby canine kidney (MDCK) cells. PCLN-1 expression decreased Na+ permeability, resulting in a decrease in the transepithelial electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 57 publications
(59 reference statements)
4
91
1
Order By: Relevance
“…Aldosterone, the primary blood pressure-regulating hormone, upreguates paracellular Cl -permeability in a rat cortical collecting duct cell line RCCD2 and hyperphosphorylates CLDN4 (38). Although we have not studied the regulation of CLDN4 channel, claudin phosphorylation was demonstrated by Ikari et al (39) to play important roles in targeting claudin-16 to TJ. CLDN4 KO animal studies are currently under way to elucidate the in vivo role of CLDN4 in blood pressure control.…”
Section: Discussionmentioning
confidence: 79%
“…Aldosterone, the primary blood pressure-regulating hormone, upreguates paracellular Cl -permeability in a rat cortical collecting duct cell line RCCD2 and hyperphosphorylates CLDN4 (38). Although we have not studied the regulation of CLDN4 channel, claudin phosphorylation was demonstrated by Ikari et al (39) to play important roles in targeting claudin-16 to TJ. CLDN4 KO animal studies are currently under way to elucidate the in vivo role of CLDN4 in blood pressure control.…”
Section: Discussionmentioning
confidence: 79%
“…The phosphorylation of claudin proteins is well-established and other claudins have been shown to be phosphorylated by various protein kinases. For example, claudin-1 is phosphorylated at Thr203 probably by MAPK [29], claudin-5 at Thr207 [32], claudin-16 at Ser217 [37], and claudin-4 by EphA2 at Tyr208 [35]. In addition claudin-1 and -4 are substrates for the WNK kinase, although no putative sites have been reported [33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated the involvement of various kinases in the phosphorylation and regulation of claudin proteins [29][30][31][32][33][34][35][36][37], and we have recently shown that phosphorylation of claudin-3 by PKA can affect TJ properties in ovarian cancer cells [38]. Protein kinase C (PKC) isoforms are present in ovarian cancer and are known to modulate TJ function by phosphorylation of the proteins in the complex [24,34,[39][40][41][42][43], but it is unclear whether PKC can directly phosphorylate and regulate claudin proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Another reported target of PKA phosphorylation is claudin-16. In the study by Ikari et al (48), claudin-16 acted as a Mg 2ϩ -selective pore when heterologously expressed in MDCKII cells. This effect was associated with constitutive phosphorylation of claudin-16 and was reversed by adding inhibitors of PKA and adenylate cyclase, or by introducing the point mutation Ser217Ala.…”
Section: Phosphorylation Of Claudinsmentioning
confidence: 99%
“…As discussed in the previous section, the in vitro studies of claudin-16 permeability properties have yielded conflicting results, and the idea that claudin-16 by itself forms a Mg 2ϩ pore is not well supported by the available evidence (44,48,57). There are two alternative models that have been proposed to explain the pathogenesis of the disease.…”
Section: Role Of Claudins In Human Diseasesmentioning
confidence: 99%